A Quasi-Static Motion Prediction Model of a Multi-Hull Navigation Vessel in Dynamic Positioning Mode - Mingyao Ji; Sharath Srinivasamurthy; Yasunori Nihei (Applied Sciences, 2022)
A Quadmaran vessel is a maritime navigation vessel with four hulls, and is expected to be utilized for high-density water quality observation in aquaculture farms. The performance of the vessel during dynamic positioning (DP) is integral to the accuracy of collected data. However, there are no models available to understand the motion characteristics of the multi-hull vessels in DP mode. Therefore, a computational model was developed to predict the DP motion of the Quadmaran vessel based on quasi-static assumptions. The fluid forces on the hulls, the thrust force of the propellers, and the external wind forces are modelled systematically, assuming the average speed while in DP does not exceed 0.25 m/s. A series of oblique towing tests and static turning tests were conducted on a 1/3 scale model to determine the hydrodynamic coefficients, while the Propeller Open Test was conducted to survey the propeller performance. The wind load was also incorporated into the computational model. Experimental validation tests were conducted in calm water and actual sea areas, and the correlation between experiment and simulation results was good. We concluded that the computational model can predict the DP motion of the Quadmaran vessel with an accuracy of roughly 2 m.